Sains Modern dan Urgensi Sentralitas Nilai Transenden dalam Pengembangan Ilmu Pengetahuan - Afith Akhwanudin (LPPM IAIN Sultan Amai Gorontalo, 2019)
Originally the Western sciences and civilization rooted in Oriental traditions. Nevertheless, Western renaissance, the Scientific Revolution has indicated a contrary paradigm in the sciences of nature. A new and alien paradigm which is totally different in its perspective and Weltanschauung from the sciences of the great Oriental traditions. The West arose with the materialistic paradigm resulted in the secularization of the cosmos. It was regarded as the beginning of the Enlightenment dissolved Dark Age scientific stagnation. Modern people have been hollowed, isolated from others by individualism then self-separated from God by egocentrism. Western objectivity negated transcendental aspects; thus, non-observable means no exist. Metaphysics, Cosmology, Epistemology, Psychology, and Ethics are not elaborated anymore to convince the Real. Such a paradigm would put worldly benefits before humanity for the sake of growth and progress. These profane sciences result in radical separation of philosophy and theology, knowledge and faith, religion and science, as well as theology and all aspects of human life. Desecration of contemporary sciences is the product of modern worldview which negated transcendent values ​​in scientific activity. This desecration became the turning point of traditionalist thinkers’ criticism with a theistic worldview to restore spiritual values ​​in sciences. Thus, worldview could produce tawhid based scientific epistemology creates unity between religion and science, knowledge and values ​​as well as the material and metaphysical then makes the humanity before the science